Harga atau Variasi Produk? Mengungkap Determinan Keputusan Pembelian Konsumen pada Usaha Ritel Lokal - Gilda Farisiane Latekay; Jusak Ubjaan; Eduard Yohannis Tamaela (Univiversitas Dr. Djar Wattiheluw, 2025)
The rapid growth of the retail sector has intensified market competition, requiring local retailers to better understand the factors influencing consumer purchasing decisions. This study examines the effects of price and product variety on purchasing decisions at Tomia Baru Mart Masohi. A quantitative survey was conducted using purposive sampling involving 107 consumers who had previously shopped at the store. Data were collected through structured questionnaires and analyzed using multiple linear regression with SPSS. The results indicate that both price and product variety have positive and significant effects on purchasing decisions, both individually and simultaneously. These findings suggest that competitive pricing and diverse product offerings play an important role in encouraging consumer purchases. The study supports consumer behavior and marketing mix theories by confirming the strategic importance of price and product variety in local retail settings. Practically, the findings provide insights for local retailers to improve pricing strategies and product assortment in order to enhance competitiveness, customer satisfaction, and long-term business performance. The study also enriches the limited empirical evidence on consumer purchasing behavior in local retail businesses in Eastern Indonesia.